If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x(x + 2y + -7) = 0 Reorder the terms: -5x(-7 + x + 2y) = 0 (-7 * -5x + x * -5x + 2y * -5x) = 0 Reorder the terms: (35x + -10xy + -5x2) = 0 (35x + -10xy + -5x2) = 0 Solving 35x + -10xy + -5x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(7 + -2y + -1x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(7 + -2y + -1x)' equal to zero and attempt to solve: Simplifying 7 + -2y + -1x = 0 Reorder the terms: 7 + -1x + -2y = 0 Solving 7 + -1x + -2y = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -1x + -7 + -2y = 0 + -7 Reorder the terms: 7 + -7 + -1x + -2y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x + -2y = 0 + -7 -1x + -2y = 0 + -7 Combine like terms: 0 + -7 = -7 -1x + -2y = -7 Add '2y' to each side of the equation. -1x + -2y + 2y = -7 + 2y Combine like terms: -2y + 2y = 0 -1x + 0 = -7 + 2y -1x = -7 + 2y Divide each side by '-1'. x = 7 + -2y Simplifying x = 7 + -2ySolution
x = {0, 7 + -2y}
| 7x^2y+4xy^2-6xy+y= | | 10b-3b= | | X^3+x^2-6x-6=0 | | 8b+9m=21.40 | | 3x(x+3)=(x+3)(x+3) | | X-15+3(X+1)=5(X-2)+11 | | 5a-12=4a | | -4000-40-(-4)= | | -3X+5-4(X-1)=-2(X+1)-24 | | 6y+-18=8y | | y=3x+9 | | 11a-8b=4a=8b=44 | | X^2-4x+15=7-13x | | y=3x^2-8 | | 3(2X+3)-2(3X+2)=-3(X+2)+2 | | 4x^3+4x^2+x=0.00002 | | 42-3x=60 | | 2u+5=1 | | 16-(3-9b)=8+7b+5 | | -2p^2+6p+3=0 | | -p^2+6p+3=0 | | (3x-2)(5x+4)=0 | | 272-37x=-45x | | 9x+3=4x+9 | | x^2-10x=37 | | (2x^2+3x-6)+(x^2-18x+6)= | | 4x-6=-14 | | 2x^4+16x^2=4 | | 3x-8=20x+26 | | x^2+14x=-10 | | 2((42-3x)+x)=60 | | 3x^2-10x+8= |